Revisionary Historical Metatext or 'Good Mills and Boon'?: Gender, Genre, and Philippa Gregory's The Other Boleyn Girl - Kennedy, Victoria (Pivot: A Journal of Interdisciplinary Studies and Thought, 2016)
In recent decades, literary critics have become increasingly interested in the ways that contemporary historical novels are used to write “history from below.” In On Lies, Secrets, and Silence (1978), Adrienne Rich describes a process she calls “re-visioning,” a process that is defined as “looking back, of seeing with fresh eyes, of entering an old text from a new critical direction” (35). Many female authors of contemporary historical novels engage in exactly this process, looking back in time and reinserting the histories of women into the dominant narrative of history in which they are often excluded or marginalized. Novelists like Philippa Gregory, Diana Gabaldon, and Tracy Chevalier have made feminist politics clearly visible in their bestselling historical novels. And yet, for all their potential and visible disruptions of patriarchal ideology, many of these popular novels also make use of literary archetypes, tropes, and narrative patterns that reinstate hegemonic ideologies about individual identity and social structure. Using Philippa Gregory’s The Other Boleyn Girl (2001) as a case study, this paper argues that popular women’s historical novels often exist in tension between the pulls of revisionary feminist historiography and the popular romance narrative.